Nontraumatic Hypotension and Shock in the Emergency Department and the Prehospital setting, Prevalence, Etiology, and Mortality: A Systematic Review - Holler, Jon Gitz (PLoS One, 2015)
BACKGROUND: Acute patients presenting with hypotension in the prehospital or emergency department (ED) setting are in need of focused management and knowledge of the epidemiology characteristics might help the clinician. The aim of this review was to address prevalence, etiology and mortality of nontraumatic hypotension (SBP ≤ 90 mmHg) with or without the presence of shock in the prehospital and ED setting. METHODS: We performed a systematic literature search up to August 2013, using Medline, Embase, Cinahl, Dare and The Cochrane Library. The analysis and eligibility criteria were documented according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA-guidelines) and The Cochrane Collaboration. No restrictions on language, publication date, or status were imposed. We used the Newcastle-Ottawa quality assessment scale (NOS-scale) and the Strengthening the Reporting of Observational studies in Epidemiology (STROBE-statement) to assess the quality. RESULTS: Six observational studies were considered eligible for analysis based on the evaluation of 11,880 identified papers. Prehospital prevalence of hypotension was 19.5/1000 emergency medicine service (EMS) contacts, and the prevalence of hypotensive shock was 9.5-19/1000 EMS contacts with an inhospital mortality of shock between 33 to 52%. ED prevalence of hypotension was 4-13/1000 contacts with a mortality of 12%. Information on mortality, prevalence and etiology of shock in the ED was limited. A meta-analysis was not feasible due to substantial heterogeneity between studies. CONCLUSION: There is inadequate evidence to establish concise estimates of the characteristics of nontraumatic hypotension and shock in the ED or in the prehospital setting. The available studies suggest that 2% of EMS contacts present with nontraumatic hypotension while 1-2% present with shock. The inhospital mortality of prehospital shock is 33-52%. Prevalence of hypotension in the ED is 1% with an inhospital mortality of 12%. Prevalence, etiology and mortality of shock in the ED are not well described.